ESCAPE ROOM: Humanizing Nursing Education in Mental Health (Research, Society and Development, 2026)
Objective: To describe the experience of applying an Escape Room as an innovative pedagogical strategy in mental health education for technical nursing training. Method: This qualitative experience report was conducted with 21 students and employed gamification, interactive questionnaires (Google Forms), and progressive QR code–based puzzles focused on reviewing the content of a curricular unit. Results: The activity promoted student engagement, enabling critical content review and reflection on the humanization of care. Fifteen of the nineteen participants completed all challenges within the stipulated time of 20 minutes. Conclusion: The methodology proved to be an effective active learning tool; however, its implementation requires adaptation to the institutional context and systematic evaluation of educational outcomes.